2008
DOI: 10.3138/cja.27.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Where Would You Turn for Help? Older Adults' Awareness of Community Support Services

Abstract: Previous findings on older adults' awareness of community support services (CSSs) have been inconsistent and marred by acquiescence or over-claiming bias. To address this issue, this study used a series of 12 vignettes to describe common situations faced by older adults for which CSSs might be appropriate. In telephone interviews, 1,152 adults aged 50 years and over were read a series of vignettes and asked if they were able to identify a community organization or agency that they may turn to in that situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…Income was fairly normally distributed across the sample with 12% reporting income below $20 000; 22% reporting income between $20 000 and $40 000 and 17% reporting income above $80 000. Comparisons to data on Hamilton from the Canadian Census shows that the sample was disproportionately female, Canadian born, had English as a first language and more respondents had higher levels of education than is true for residents of Hamilton (Denton et al. 2008).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Income was fairly normally distributed across the sample with 12% reporting income below $20 000; 22% reporting income between $20 000 and $40 000 and 17% reporting income above $80 000. Comparisons to data on Hamilton from the Canadian Census shows that the sample was disproportionately female, Canadian born, had English as a first language and more respondents had higher levels of education than is true for residents of Hamilton (Denton et al. 2008).…”
Section: Resultsmentioning
confidence: 90%
“…As suggested in the literature review, not knowing or understanding how to access the needed services is a major barrier to service use (Silverstein 1984, Gallagher & Truglio‐Londrigan 2004). Analysis presented elsewhere (Denton et al. 2008) shows that about one‐quarter of our respondents would seek information about CSSs from information and referral services, the telephone book, doctor’s offices and from informal sources such as discussions with friends, neighbours and family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older women who feel that they are in control of the events in their lives have been found to have lower levels of depression, activity limitation and psychosocial symptoms while having increased longevity and better self-rated health (Denton, 2009). Data from the AHEAD survey (Asset and Health Dynamics of the Oldest Old) found that limitations in mobility and performing self-care were correlated with high depressive symptoms in women 70 and older (Bould, 2008).…”
Section: Depression (Control Variable)mentioning
confidence: 99%